SOME ASPECTS OF SOUTH ASIA'S GROUNDWATER IRRIGATION ECONOMY: ANALYSES FROM A SURVEY IN INDIA, PAKISTAN, NEPAL TERAI AND BANGLADESH - Shah T.; Singh O.P.; Mukherji A. (My University, 2006)
Since 1960, South Asia has emerged as the largest user of groundwater in irrigation in the world. Yet, little is known about this burgeoning economy, now the mainstay of the region's agriculture, food security and livelihoods. Results from the first socio-economic survey of its kind, involving 2,629 well-owners from 278 villages from India, Pakistan, Nepal Terai and Bangladesh, show that groundwater is used in over 75% of the irrigated areas in the sample villages, far more than secondary estimates suggest. Thanks to the pervasive use of groundwater in irrigation, rain-fed farming regions are a rarity although rain-fed plots within villages abound. Groundwater irrigation is quintessentially supplemental and used mostly on water-economical inferior cereals and pulses, while a water-intensive wheat and rice system dominates canal areas. Subsidies on electricity and canal irrigation shape the sub-continental irrigation economy, but it is the diesel pump that drives it. Pervasive markets in tubewell irrigation services enhance irrigation access to the poor. Most farmers interviewed reported resource depletion and deterioration, but expressed more concern over the high cost and poor reliability of energy supply for groundwater irrigation, which has become the fulcrum of their survival strategy.
Keywords: AGRICULTURE; SOUTH ASIA; GROUNDWATER DEVELOPMENT; WELL-OWNER SURVEY; SOCIO-ECONOMIC ASPECTS